Discrete spectrum of zero order pseudodifferential operators - Rozenblûm, Grigorij Vadimovič (Wydawnictwa AGH, 2023)
We study the rate of convergence of eigenvalues to the endpoints of essential spectrum for zero order pseudodifferential operators on a compact manifold.
Opuscula Mathematica
Bibliogr. 266-268.
Keywords: pseudodifferential operators; eigenvalue asymptotics